Visões do urbano: a rua XV de Novembro, Pelotas/RS - Devantier, Vanessa da Silva (2013)
This work aims to study a cultural reference of Pelotas/RS, the 15th of November Street, in their central stretch, Coronel Pedro Osório Square to the Voluntários da Pátria Street, through periodic press, expressed in the newspapers A Opinião Pública and Diário Popularbetween the years 1920 to 1950. At the time focused, this stretch of the route was seen as the main area of commerce, culture and leisure in the city of Pelotas/RS. Three points were highlighted: trade, rides and carnival, elements that characterize this urban space as a benchmark of their history and culture.From the journals, columns, notes, chronicles and photographs are understood asvisions of urban, considerable parts of newspapers dedicated to the city in their daily lives, their problems and their transformations. As central street of Pelotas at least until the first half of the twentieth century, the 15th of November Street stood out as important focus for these different looks, understood as the window of a city that was intended modern, cultured and progressive